Analisis Penurunan Reject Pakan Tenggelam pada Mesin Extruder di PT. X Gresik - Alfin Kusuma; Jani Rahardjo (Jurnal Titra, 2021)
PT. X is a manufacturing company that produce animal feed such as fish and shrimp feed. In 2020, total product defect rate for floating fish feeds occasionally exceeds the determined threshold. Because of that PT. X planned to uphold its product quality to its determined level thereby the customer will be satisfied with products and sustain the company. Pareto Diagram, Fishbone chart, and 5-whys analysis method are used to find the root causes of the problem and the type of defects that has to be eliminated in this research.  The root causes that has been identified yielded several improvement such as adding automatic machine, create standardization for raw material, create module, and conduct training for the opeartor. Operator training is the improvement chosen by the company's criteria. After observation from the percentage of defect by two sample t test, it is shown that training for the production machine operator do not yield significant impact. The average of reject after implementation is not too different from the average defect before implementation.